2016
DOI: 10.1177/0165025416631832
|View full text |Cite
|
Sign up to set email alerts
|

Social-psychological and educational outcomes associated with peer victimization among Korean adolescents

Abstract: This study examines the effects of peer victimization by verbal, physical, and relational bullying on Korean adolescents' self-worth, disconnect to peers, school engagement, and academic achievement. A two-year longitudinal survey on 3,266 sixth-graders attending school in Seoul, Korea was used. Multivariate regression results controlling for socio-demographic characteristics as well as initial levels of outcome indicated that youth bullied by their peers experienced greater difficulties than non-bullied peers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
0
5
0
3
Order By: Relevance
“…Peer pressure is influence of a peer group, observers or individual exerts that encourages others to change their attitudes, values, or behaviour to conform to groups. Peers exert a significant influence on behaviour during adolescence15. Peer pressure is commonly associated with events of adolescent risk taking (such as delinquency, drug abuse, sexual behaviours, and reckless driving) because these activities commonly occur in the company of peers16.…”
Section: Introductionmentioning
confidence: 99%
“…Peer pressure is influence of a peer group, observers or individual exerts that encourages others to change their attitudes, values, or behaviour to conform to groups. Peers exert a significant influence on behaviour during adolescence15. Peer pressure is commonly associated with events of adolescent risk taking (such as delinquency, drug abuse, sexual behaviours, and reckless driving) because these activities commonly occur in the company of peers16.…”
Section: Introductionmentioning
confidence: 99%
“…Nesse sentido, foram encontrados 14 estudos que investigaram associações entre envolvimento em bullying e engajamento escolar, sendo que destes 12 eram empíricos (Buda & Szirmai, 2010;Cho & Choi, 2017;De Laet et al, 2015;Dorio et al, 2018;Iyer et al, 2010;Li et al, 2011;Mehta et al, 2013;Nakamoto & Schwartz, 2011;Perdue et al, 2009;Ripski & Gregory, 2009;Totura et al, 2014;Wang & Eccles, 2012) e dois teóricos ou de revisão de literatura (Herald-Brown et al, 2007;Juvonen, 2007). Estes estudos apontaram evidências de que o envolvimento em bullying está correlacionado negativamente com o engajamento escolar dos alunos.…”
Section: Envolvimento Em Bullying E Engajamento Escolarunclassified
“…Assim, de maneira geral, aponta-se que o bullying está negativamente correlacionado ao engajamento escolar, sendo que alunos que percebem ou se envolvem em situações de bullying apresentam menor engajamento escolar (Cho & Choi, 2017;Dorio et al, 2018;Iyer et al, 2010;Mehta et al, 2013;Perdue et al, 2009). Por outro lado, um bom relacionamento com pares está positivamente associado ao engajamento escolar, portanto, alunos que percebem aceitação e apoio por parte dos colegas tendem a apresentar maior engajamento escolar (Perdue et al, 2009).…”
Section: Envolvimento Em Bullying E Engajamento Escolarunclassified
“…Olweus (1978) established systematic, psychological research on bullying, since then bullying can be identified as a significant, widespread public health problem (Hellström et al , 2015). The effects of bullying can be associated with: suicide, suicide ideation and planning (Roh et al , 2015; Bell et al , 2014); mental health implications (Busch et al , 2015; Lereya et al , 2015); physical health implications and health risk behaviour (Stuart and Jose, 2014; Azagba, 2016); impact on social functioning (Feldman et al , 2014; Hutzell and Payne, 2012) and self-image (Cho and Choi, 2016); criminality (Decamp and Newby, 2015; Wong and Schonlau, 2013); and impaired cognition (Ponzo, 2013). Successful anti-bullying intervention suggests schools, communities, and parents should take a shared and active role in attending anti-bullying workshops, training, and meetings so that they; understand the definitive features of bullying, collectively enforce rules, and productively supervise behaviour (Olweus, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Identity (Wolke, Woods, Bloomsfield & Karstadt, 2000). Pure victims can be characterised as being socially isolated (Cho & Choi, 2016) and rejected by their peers (Ortega et al, 2012).…”
mentioning
confidence: 99%